EVALUATION OF CARNAUBA PROGENIES AND ESTIMATES OF GENETIC PARAMETERS IN THE JUVENILE PHASE - LUNARA GRAZIELLY COSTA DA SILVA; JEFFERSON FRANCISCO LIMA MOREIRA; HERICLES BRUNO BEZERRA HOLANDA; EMANUEL LUCAS BEZERRA ROCHA; POLIANA COQUEIRO DIAS (Revista Caatinga, 2018)
Carnauba (Copernicia prunifera) is a forest species with multiple uses, and is of great economic and social importance for several communities involved in extractive agriculture in northeastern Brazil. However, there are few studies on genetic variability in this species. Thus, this work aimed to produce information about the genetic characterization of C. prunifera seeds and seedlings, using provenance and progeny evaluations. A progeny test was performed in a plant nursery, using seeds of 36 matrices sampled in the municipalities of Mossoró and Apodi (Rio Grande do Norte State), and Russas and Icapuí (Ceará State). Three groups were derived according to the spatial distance between the collected matrices. Biometric analyses of the seeds were performed, adopting a completely randomized experimental design, with four replicates of 25 seeds in each analysis. A randomized block design (five replicates and five plants per plot) was used at the seedling production phase. The data evaluated included the emergence speed index, emergence percentage, leaf size, leaf base diameter, and survival (at 30, 60, and 90 days after sowing). The restricted maximum likelihood method was used in the statistical analysis, with the aid of SELEGEN software. In order to evaluate genetic variability in the C. prunifera population samples, it was verified that the juvenile characters presented a moderate genetic control. The three groups of spatially delimited matrices presented no significant genetic differences. This information may assist in the development of forestry practice for this species.